"A Collision between Beauty and Ugliness": An Interview with Richard Misrach. Issue 2 (3rd July 2017) - Hoelscher, Steven
Abstract : For two days in August 2010, the author conducted an oral history interview with photographer Richard Misrach in his Emeryville, California, studio. One of the most influential photographers working today, Misrach has produced an impressive body of work that spans nearly five decades and consistently garners critical, international attention. His meticulously rendered, large-scale color photographs focus on the relationship between humans and their environments. Sponsored by the Smithsonian's Archives of American Art, the interview, edited for brevity and clarity, reveals a photographer highly cognizant of both the long history of photography that proceeds him as well as the changing nature of the art world and the market that sustains it. He reflects on the larger national myths that specific places—most notably, the American West, but also the Deep South, and the Southwest borderlands—are asked to carry, and the often toxic results that ensue. A nuanced, progressive sense of place becomes evident as Misrach describes how his personal way of interacting with the world, both to affect social change and to live one's life, is to photograph it. He eschews categories that critics regularly use to define his work, and he speaks evocatively about the geographies that have defined his career. Altogether, the interview sheds light on the geographic imagination and working process of a photographer who bridges the concerns of geography and the humanities in ways that are evocative, confrontational, and thought-provoking.